Empagliflozin targeting STAT3/Akt/Nrf2 axis promoting diabetic wound healing in rat model - Magadmi, Rania; Alfawaz, Dalal; Bakhshwin, Ahmed; Binzomah Alghamdi, Fatmah; Alfawaz, Sultan A.; Bakhshwin, Duaa M.; Jamal, Maha H.; Sofi, Roba A.; Esmat, Ahmed (Frontiers in Pharmacology, 2025)
BackgroundDiabetes mellitus (DM) and its complications pose a major global health challenge, with impaired wound healing leading to severe outcomes. Chronic inflammation, excessive proinflammatory cells, and high reactive oxygen species contribute to diabetic wound complications. Empagliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, has antioxidant and anti-inflammatory properties, but its impact on wound healing remains unclear.ObjectiveTo investigate the effects of empagliflozin on wound healing in diabetic rats and explore its underlying molecular mechanisms.MethodologyFifty male Wistar rats were divided into five groups: untreated diabetic rats (STZ group), STZ + plain hydrogel, STZ + empagliflozin hydrogel (1%), STZ + oral empagliflozin (20 mg/kg), and STZ + MEBO®. Wounds were created 2 weeks post-STZ injection and treated for 21 days. Assessments included wound contraction, histopathology, fasting blood glucose (FBG), oxidative stress parameters, and inflammatory biomarkers in skin homogenates. Mechanistic markers, including phosphorylated STAT3, Akt, nuclear factor erythroid 2-related factor 2 (Nrf2), sirtuin 1 (SIRT1), and β-catenin, were analyzed.ResultsEmpagliflozin-treated animals had significant wound healing improvements, confirmed by macroscopic and histological assessments, with oral administration being the most effective. Inflammatory markers, including tumor necrosis factor-alpha (TNF- α) and interleukin-6 (IL-6), were markedly reduced, alongside decreased oxidative stress. Both oral and topical empagliflozin significantly upregulated key proteins involved in healing, including phosphorylated STAT3, Akt, Nrf2, SIRT1, and β-catenin.ConclusionEmpagliflozin accelerates wound healing in diabetic rats through its anti-inflammatory and antioxidant properties. Oral empagliflozin exhibited superior efficacy, suggesting systemic effects that extend beyond glycemic control. These findings offer insights into its molecular mechanisms of empagliflozin as a promising therapeutic agent for diabetic wound management.